Industri Seni Patchwork dan Quilting Motif Batik Dayak sebagai Produk Desain Interior yang Inovatif - Amiany, Amiany; Widati, Titiani; Tiawon, Harin (University of Merdeka Malang, 2021)
Selat Hilir Sub-district is one of crowded areas (slums) located near the market and riverside. In several crowded areas many stay-home mothers’ ages of 30-46 who went to school up to Junior High School (SMP) have much spare time. One of these groups is the group of RT.017 Selat Hilir Sub-district who generally manage their household without adequate skills. The potency of Home Industry Patchwork Art and Quilting of Dayak Batik as innovative interior design product can become a solution in an effort to increase family income and to increase the people’s prosperity in Selat Hilir Sub-district, by making products from wasted fabrics into a high end and high-priced products in Kuala Kapuas. Also, making such artworks and products is still something new which people of Central Borneo aren’t familiar yet. Therefore, a training is required. The training is as followed: (1) preparation of module of basic knowledge of patchwork art and quilting and try out; (2) excecution, making patterns, printing patternts to fabrics, cutting and sewing; (3) evaluation, some products from training are tablecloths, pillow cover, flower pot base, doormats and face masks. DOI: https://doi.org/10.26905/abdimas.v6i1.5041